Keeping people with epilepsy safe during the COVID-19 pandemic. (9th June 2020) - French, Jacqueline A.; Brodie, Martin J.; Caraballo, Roberto; Devinsky, Orrin; Ding, Ding; Jehi, Lara; Jette, Nathalie; Kanner, Andres; Modi, Avani C.; Newton, Charles R.; Patel, Archana A.; Pennell, Page B.; et al.
Abstract : Objectives: To provide information on the effect of the coronavirus disease of 2019 (COVID-19) pandemic on people with epilepsy and provide consensus recommendations on how to provide the best possible care for people with epilepsy while avoiding visits to urgent care facilities and hospitalizations during the novel coronavirus pandemic. Methods: The authors developed consensus statements in 2 sections. The first was "How should we/clinicians modify our clinical care pathway for people with epilepsy during the COVID-19 pandemic?" The second was "What general advice should we give to people with epilepsy during this crisis? The authors individually scored statements on a scale of −10 (strongly disagree) to +10 (strongly agree). Five of 11 recommendations for physicians and 3/5 recommendations for individuals/families were rated by all the authors as 7 or above (strongly agree) on the first round of rating. Subsequently, a teleconference was held where statements for which there was a lack of strong consensus were revised. Results: After revision, all consensus recommendations received a score of 7 or above. The recommendations focus on administration of as much care as possible at home to keep people with epilepsy out of health care facilities, where they are likely to encounter COVID-19 (including strategies for rescue therapy), as well as minimization of risk of seizure exacerbation through adherence, and through ensuring a regular supply of medication. We also provide helpful links to additional helpful information for people with epilepsy and health providers. Conclusion: These recommendations may help health care professionals provide optimal care to people with epilepsy during the coronavirus pandemic.